The correlation between dyslexia and social and demographic factors in children of school age. - Apostolara P; Tsoumakas K; Diomidous M; Kalokerinou A (Nosileftiki, 2010)
Background: The numbers of children with learning disabilities are increasing. Recently efforts have been made to identify the biological, hereditary and social factors that may trigger and aggravate the phenomenon. Aim: To investigate the correlation of social and demographic factors with the appearance of dyslexia in children of school age. Method: The study group was a convenience sample of 100 children (50 with diagnosed dyslexia and 50 with no diagnosis of learning problems), aged 6 to 12 years, from 3 schools in Attica, recruited over a 2-month period. Questionnaires covering demographic data and factors that may be connected with the presence of dyslexia were distributed to the children's parents. The response rate was 96%. Logistic regression analysis was used in order to identify independent factors associated with dyslexia. Results: The proportion of dyslexia was lower in girls than in boys (OR=0.21, 95% CI: 0.04-0.98, p=0.05) and it was more frequent in left-handers (OR=7.58, 95% CI: 1.01-62.5, p=0.05). Increased likelihood of dyslexia was correlated with poor concentration (OR=52.61, 95% CI: 7.88-351.1, p<0.001), articulation- phonology disorders (OR=11.51, 95% CI: 1.01-130.73, p=0.05), a family history of dyslexia (OR=35.68, 95% CI: 5.02-253.33, p=0.003) and having a father in a 'middle class' profession. Finally it was found that children who had achieved night-time bladder control at 2-3 years were less likely, by 82%, to be dyslexic than children who achieved bladder control later than 3 years of age (p=0.043). Conclusions: Apart from biological factors, the findings of this study suggest that factors such as sex, left-handedness, family history and parental educational level are correlated with dyslexia.